How to be cooler than cool - Taylor, Sean 1965- (Walker Books, 2021)
Cat has found a pair of sunglasses. She thinks they are going to make her look COOL. "I'm not just any old cat at the playground," she says. "I'm a real cool cat, gliding backwards down the slide, looking cooler than cool. WITH EXTRA COOL ON TOP!" She pops on the glasses confidently struts forwards and Meooaaaooow! falls down the slide. Oh, how UNCOOL. Can Pig or Cockatoo do any better?
Keywords: Sonnenbrille; Katze; Tiere; Animals / Juvenile fiction; Sunglasses / Juvenile fiction; Lunettes de soleil / Romans, nouvelles, etc. pour la jeunesse; Bilderbuch